Teenagers’ Language Use in Batam: Language Variation - Suhardianto, Suhardianto (Universitas Muhammadiyah Jember, 2016)
This research is aimed to figure out the phenomenon of language variation that is used among teenagers in Batam. The language variations which are created by teenagers contrast to the standard language formula. The aplication of that language can massively affect the standard language used in every formal situation. Knowing the basic knowledge about the variation, how are the process of constructing the non-standard language and the aspect of language can help the teenagers to avoid the devastating of standard language. The result of the research showed that in daily conversation among teenagers in Batam, the teenagers mostly used the non-standard language in their interaction involving the slang and colloquial languages. The use of these languages were frequently mixed by other languages, such as English language and regional language that teenagers imitated from Jakarta. Moreover, teenagers mostly used the slang and colloquial languages in the informal situation.Keywords: Language variation, slang, colloquial.